-5.7m-2.2m=23.7

Simple and best practice solution for -5.7m-2.2m=23.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5.7m-2.2m=23.7 equation:


Simplifying
-5.7m + -2.2m = 23.7

Combine like terms: -5.7m + -2.2m = -7.9m
-7.9m = 23.7

Solving
-7.9m = 23.7

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-7.9'.
m = -3

Simplifying
m = -3

See similar equations:

| 7.2=8.6-0.7x | | f(x+6)=5x+5 | | 2x^2+9x+8= | | 5x+4-2=(x+8) | | 6s+(4s-20)=450 | | 7x-3=4-2x | | -6+4(3x-13)=82 | | 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 |

Equations solver categories